Chapter The Dutch Republic as Example of Maritime Transport Services Clusters in Preindustrial Europe (ca. 1650-1800) - Scheltjens, Werner (Atti delle «Settimane di Studi» e altri Convegni, 2019)
By means of a comparative analysis of the 'Dutch case' with the Saintonge in South-West France and Bohuslän in South-West Sweden, this paper analyses the rise and decline of maritime services clusters in preindustrial Europe. The leading question for this comparative analysis is: Was the 'Dutch case' exceptional or can similar developments be recognised in other parts of Europe as well? A survey of the regional economic origins of communities of maritime transporters is combined with analyses of their operations and institutions. Relying on primary sources, the paper addresses the contribution of a great many 'anonymous' people, that literally connected the 'nodes' in international maritime trade networks, but whose contribution to the preindustrial European economy has been assumed a priori rather than thoroughly investigated.